Is conceptual learning based on conceptual change text (CTT) effectively applied to PGSD students' science classes? - Wati Sukmawati; Sri Lestari Handayani; Yeni Yeni (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2021)
For Elementary School Teacher Education (PGSD) students, the introductory science concept course is part of the compulsory course. The understanding of PGSD students in basic science concepts will affect the quality of learning in the classroom. This research was conducted in odd semesters with 60 students who attended lectures on basic science concepts, and the sample selection was made randomly. To collect data on the effectiveness of the implementation of CCT, instruments used in the form of cognitive and clinical test questions have gone through validation and reliability tests. Students were divided into two groups in the study: the experimental group using CCT-based contextual learning as teaching materials and the control class using ordinary teaching materials. Based on the N-Gain data found in the field, there was a significant difference between the experimental and control groups; the control class had an N-Gain value of 0.54, while the experimental class was 0.81. The data revealed that learning using CCT successfully increased students' understanding of concepts in the material cycle and created a better environment compared to the control class. However, based on interview data, both experimental and control class students were interested in learning the concept of the energy cycle and environmental pollution, and there was no significant difference.